2015
DOI: 10.3233/jad-150199
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and Its Relationship with Macular Pigment Optical Density and Serum Concentrations of its Constituent Carotenoids

Abstract: Background: Macular pigment (MP) levels correlate with brain concentrations of lutein (L) and zeaxanthin (Z), and have also been shown to correlate with cognitive performance in the young and elderly.Objective: To investigate the relationship between MP, serum concentrations of L and Z, and cognitive function in subjects free of retinal disease with low MP (Group 1, n = 105) and in subjects with AMD (Group 2, n = 121).Methods: MP was measured using customized heterochromatic flicker photometry and dual-wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 87 publications
5
28
1
Order By: Relevance
“…Mulder et al, 2014), that study based the analysis on plasma lutein and self-reported dietary intake of lutein while our study used MPOD, a retinal measure which may be more sensitive to cognitive measures than serum lutein. Kelly et al(2015) found that in adults, both macular pigment and serum lutein were associated with cognitive outcomes, but only the associations with macular pigment remained after controlling for relevant characteristics like sex, age, diet, and education level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mulder et al, 2014), that study based the analysis on plasma lutein and self-reported dietary intake of lutein while our study used MPOD, a retinal measure which may be more sensitive to cognitive measures than serum lutein. Kelly et al(2015) found that in adults, both macular pigment and serum lutein were associated with cognitive outcomes, but only the associations with macular pigment remained after controlling for relevant characteristics like sex, age, diet, and education level.…”
Section: Discussionmentioning
confidence: 92%
“…For example, lutein has been shown to correlate with many measures of cognition in healthy older adults (Vishwanathan, Iannaccone, et al 2014), adults with advanced macular degeneration (Kelly et al 2015), and those with mild cognitive impairment (Renzi et al 2014). Verbal fluency and memory have been shown to improve after supplementation of lutein and DHA in healthy older women (Johnson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also confirmed the presence of L and Z in the non-human primate brain (24) and the human brain (25)(26)(27) , and in concentrations that are proportional to retinal concentrations of these carotenoids. Interestingly, there is a growing body of evidence that these carotenoids may be important in maintaining optimal cognitive function (28)(29)(30)(31) .…”
mentioning
confidence: 99%
“…We excluded 13 relevant studies for using interventions other than carotenoids or its derivatives alone [52][53][54][55][56][57][58][59][60][61], not conducting cognitive assessment [62], and lack of a RCT [63].…”
Section: Excluded Studiesmentioning
confidence: 99%